Long-term stability of vocal individuality cues in a territorial and monogamous seabird - Calcari, Chiara; Pilenga, Cristina; Baciadonna, Luigi; Gamba, Marco; Favaro, Livio (Animal cognition, 2021)
The stability of individual acoustic features is fundamental in social species, and more importantly in monogamous and territorial species, showing long-term fidelity both to the partner and the breeding site. In this study, the stability over time of two discrete vocal types was investigated in the African penguin ( Spheniscus demersus ), a monogamous and territorial seabird. Contact calls and ecstatic display songs were recorded from an ex situ colony in 2017 and in 2020. For each vocalisation, we measured 14 spectral and temporal acoustic parameters related to both source and filter components. Two separate leave-one-out cross-validated Discriminant Function Analyses (DFA) were then performed, generating the discriminant functions from the vocalisations collected in 2017 to classify those recorded in 2020. The DFA correctly classified 62% of the contact calls (10 subjects) and 80.9% of the ecstatic display songs (seven subjects) according to the correct emitter, showing that acoustic cues to individuality encoded in both vocal types remained unchanged over four consecutive breeding seasons. We suggest that, in this monogamous and territorial bird species, individual acoustic stability could be selected for to identify groupmates and neighbours over the years and to help couples to reunite in consecutive breeding seasons, increasing individual fitness.